Ni-Co-based deformed high-strength high-entropy high-temperature alloy with high-content square gamma'coherent strengthening at 850 DEG C and preparation method of Ni-Co-based high-strength high-entropy high-temperature alloy

Through cluster composition design and precise control of element ratios, a Ni-Co based deformable high-strength and high-entropy high-temperature alloy was prepared, which solved the problems of insufficient deformation ability and structural stability of existing alloys at high temperatures and achieved excellent structural stability and high strength at high temperatures.

CN120683411APending Publication Date: 2025-09-23DALIAN UNIV OF TECH +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510798451.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

Existing deformable high-temperature alloys are difficult to maintain excellent deformation ability and high-temperature structural stability at high temperatures, especially above 800°C, where the alloy performance decreases significantly, and added elements easily form harmful phases, affecting the alloy performance.

Method used

A cluster composition design method is adopted to precisely control the element ratio in the Ni-Co based high-temperature alloy to form a high-content square γ′ coherent strengthening phase. Through vacuum arc melting, homogenization treatment, cold rolling and aging treatment, a Ni-Co based deformable high-strength and high-entropy high-temperature alloy for use at 850℃ with high-content square γ′ coherent strengthening is prepared.

Benefits of technology

The stability of the γ/γ′ coherent structure at 850°C is achieved. No harmful phase is precipitated after long-term aging at 850°C. The alloy has excellent high-temperature structure stability and high strength. The room temperature yield strength is >1000MPa, and the high-temperature yield strength at 800°C is >850MPa, maintaining good deformation processing capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120683411A_ABST
    Figure CN120683411A_ABST
Patent Text Reader

Abstract

The invention relates to a Ni-Co-based deformed high-strength high-entropy high-temperature alloy with high-content square gamma'coherent strengthening at 850 DEG C and a preparation method of the Ni-Co-based deformed high-strength high-entropy high-temperature alloy, and belongs to the field of deformed high-entropy high-temperature alloys, the Ni-Co-based deformed high-strength high-entropy high-temperature alloy comprises Ni, Co, Al, Ti, Nb, Ta, Cr, Mo, W, C, B and Zr, and comprises the following alloy components in percentage by mass (wt.%): 35.1-37.7% of Co, 2.6-2.7% of Al, 2.8-3.3% of Ti, 0.6-2.8% of Nb, 0-1.3% of Ta, 8.4-12.5% of Cr, 2.9-3.9% of Mo, 5.5-5.9% of W According to the invention, coherent precipitation of square L12-gamma'phase particles on an FCC-gamma matrix is realized through alloy design, the total volume percentage of the gamma 'phase is 45-60%, the alloy shows excellent gamma / gamma' coherent structure stability after long-term aging at 850 DEG C, and no other harmful phases are precipitated, so that the alloy has good mechanical properties and excellent processing deformability, and is suitable for industrial production. The room-temperature yield strength exceeds 1000 MPa, the room-temperature plasticity exceeds 25%, the yield strength at 800 DEG C exceeds 850 MPa, and the high-strength high-entropy high-temperature alloy is a novel deformable high-strength high-entropy high-temperature alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of deformed high-entropy high-temperature alloys and relates to a Ni-Co based deformed high-strength high-entropy high-temperature alloy for use at 850°C with high content of square γ′ coherent strengthening and a preparation method thereof. Background Art

[0002] Superalloys are metallic materials based on Fe, Co, and Ni, typically designed to operate at temperatures exceeding 600°C and under complex stresses. Ni-based superalloys, in particular, possess excellent high-temperature mechanical properties and creep resistance, making them widely used in aerospace engines and industrial gas turbines. This is primarily due to their unique microstructure, characterized by the coherent precipitation of spherical or cuboidal L12-γ′ nanoparticles within a face-centered cubic (FCC)-γ matrix. With the continuous advancement of aerospace technology, the service temperatures of hot-end components such as turbine disks have exceeded 700°C. To meet these performance requirements, various alloying elements are often added to superalloys for turbine disks, including solution-strengthening elements (Cr, Mo, W), precipitation-strengthening elements (Al, Ti, Nb, Ta), and grain-boundary-strengthening elements (C, B, Zr). However, this high degree of alloying not only increases the alloy's preparation cost but also makes it more difficult to manipulate the alloy's microstructure and properties. Furthermore, the large addition of elements such as Al, Ti, Nb, and Ta to increase the γ′ precipitate content significantly reduces the alloy's workability and results in a very narrow hot working window.

[0003] At present, it is difficult for the deformable high-temperature alloy materials used in key components such as aircraft engine turbine disks and blades to exceed 800℃. For example, the deformable high-temperature alloy represented by IN718 has excellent processing deformation ability, thanks to the high Nb content (4.75~5.50wt.%), slow diffusion of Nb element, slow nucleation rate of precipitation phase, low precipitation temperature, and large hot working window. However, the high Nb content is also prone to cause alloy element segregation. At the same time, the operating temperature of In718 alloy is limited to 650℃. Once the temperature rises, a phase transformation will occur. The main strengthening phase tetragonal structure γ″-Ni3Nb will be transformed into orthorhombic structure δ-Ni3Nb. Due to the loss of coherence with the matrix FCC-γ phase, the alloy performance is greatly reduced; subsequently, IN718Plus alloy replaces Fe with Co, increases W, and increases Al, so that ordered L12-γ′ nanoparticles are precipitated on the FCC-γ matrix to form a high-temperature structure. The stable FCC-γ / γ′ coherent microstructure increases the alloy's heat resistance to 700°C, but its processing deformability is weakened, especially in cold-rolled sheets where the elongation after fracture is less than 10%. The Ni-Co-based TMW superalloy developed by the National Institute for Materials Science in Japan can withstand temperatures up to 725°C. Co contents of 20-31 wt.%, Ti contents of 5.1-7.4 wt.%, and W contents of 1.0-2.0 wt.% improve the alloy's heat resistance to some extent. However, when the Ti content exceeds 6.0 wt.%, the harmful η-Ni3Ti phase precipitates, affecting the alloy's performance. Furthermore, the γ′ particle content of current high-strength deformable superalloys has reached 45-50%. At this point, the γ′ phase precipitation temperature is high, the hot working window is narrow, and it already falls into the category of difficult-to-deform superalloys.

[0004] Therefore, achieving excellent deformation capability while improving high-temperature performance and microstructural stability is a key issue currently hindering the development of deformable superalloys. In light of this, the present invention provides a Ni-Co-based deformable high-strength, high-entropy superalloy for 850°C deformation with high-content square γ′ coherent strengthening. This alloy maintains a stable γ / γ′ coherent microstructure after long-term aging at 850°C without harmful phase precipitation, exhibiting room temperature tensile yield strength >1000 MPa, ductility >25%, and high-temperature strength >850 MPa at 800°C. Summary of the Invention

[0005] The present invention provides a Ni-Co-based deformed high-strength, high-entropy superalloy for use at 850°C with a high content of square γ′ coherent strengthening and a preparation method thereof. Compared to existing cast and forged deformed superalloys, this alloy exhibits a high-temperature yield strength greater than 850 MPa at 800°C, and after long-term aging at 850°C, the γ / γ′ coherent structure is stable and free of harmful phase precipitation. The purpose of this invention is to develop a new type of deformed high-strength, high-entropy superalloy for aerospace applications with higher strength and higher temperature tolerance through precise alloy design.

[0006] In order to achieve the above object, the technical solution adopted in the present invention is:

[0007] A Ni-Co based deformed high-strength and high-entropy superalloy for use at 850°C with high-content square γ′ coherent strengthening, the deformed high-strength and high-entropy superalloy comprising Ni, Co, Al, Ti, Nb, Ta, Cr, Mo, W, C, B, and Zr, wherein the mass percentages (wt.%) of the alloy components are as follows: Co: 35.1-37.7, Al: 2.6-2.7, Ti: 2.8-3.3, Nb: 0.6-2.8, Ta: 0-1.3, Cr: 8.4-12.5, Mo: 2.9-3.9, W: 5.5-5.9, C: 0-0.08, B: 0-0.02, Zr: 0-0.03, Ni: balance, and the atomic percentage ratio of (Ti+Nb+Ta) / Al is 0.5-1.

[0008] The 850°C Ni-Co-based deformed high-strength and high-entropy high-temperature alloy with high-content square γ′ coherent strengthening has a specific microstructure: square L12-γ′ nanoparticles are coherently precipitated on the FCC-γ matrix, and the total volume percentage of the γ′ phase is 45-60%; after long-term aging at 850°C, there is no obvious coarsening and no harmful phase generation, and it has excellent high-temperature microstructure stability.

[0009] The typical properties of the 850°C Ni-Co based deformed high-strength and high-entropy high-temperature alloy with high content of square γ′ coherent strengthening are: room temperature yield strength>1000MPa, room temperature elongation>25%, and high temperature yield strength>850MPa at 800°C.

[0010] A preparation method for a Ni-Co based deformed high-strength and high-entropy high-temperature alloy for use at 850°C with high-content square γ′ coherent strengthening comprises the following steps: first, placing each alloy component into a vacuum arc melting furnace according to its mass percentage and melting it at least four times to obtain an alloy ingot with uniform composition; second, homogenizing the alloy ingot in a muffle furnace at a temperature of 1150-1200°C for 4-8 hours, followed by multiple unidirectional cold rolling passes with a single reduction of 0.1-1 mm and a total reduction of 85-90%; finally, solution treating at 1060-1100°C for 1-2 hours, aging treating at 850°C for 50-500 hours, and water quenching to obtain the Ni-Co based deformed high-strength and high-entropy high-temperature alloy for use at 850°C with high-content square γ′ coherent strengthening.

[0011] A Ni-Co-based deformed high-strength, high-entropy superalloy for 850°C with high-content square γ′ coherent strengthening. Its microstructure is characterized by the coherent precipitation of square L12-γ′ nanoparticles on an FCC-γ matrix. The γ / γ′ coherent structure remains stable after long-term aging at 850°C. At the same time, the high-temperature strength at 800°C exceeds 850MPa.

[0012] The idea of ​​realizing the above technical solution is to use the applicant's cluster composition design method to design the composition of a new Ni-Co based deformable high strength and high entropy superalloy. This method forms cluster structure units based on the interaction between elements, which are [clusters] (connected atoms) x , consisting of a cluster and x connecting atoms. A cluster is a coordination polyhedron formed by any solute atom as the center and surrounded by matrix atoms in the nearest-neighbor shell. Connecting atoms in the next-nearest-neighbor shell are used to match the average density of the alloy. For FCC-based alloy systems, clusters are typically cuboctahedrons with a coordination number of CN12, and the number of connecting atoms is typically x = 3-5. This cluster-based composition design approach has been successfully applied to the design of various engineering alloys, including high-temperature austenitic stainless steel, low-elastic β-Ti alloys, and Co-based superalloys, providing new insights and methods for the compositional design of high-performance engineering alloys.

[0013] According to the applicant's previous work, in the Ni-Co based high temperature alloy system, according to the role played by the elements in the alloy, they can be divided into Ni-like (containing Ni, Fe, Co), Cr-like (containing Cr, Mo, W), and Al-like (containing Al, Ti, Nb, Ta). To simplify the expression, the three cluster elements are written as in, The mixing enthalpy of the element with the matrix element is relatively negative, the interaction is strong, and the element preferentially occupies the central atomic position; Elements will preferentially occupy cluster positions, forming Clusters, excess content enters the connecting atomic position; the mixing enthalpy with the matrix element is positive, and the interaction is weak Elements occupy the connecting atomic positions. By analyzing a large number of deformed high-temperature alloys, the composition formula of the new deformed high-entropy high-temperature alloy cluster can be obtained as follows:

[0014] In new high-entropy superalloys, Elements primarily form the γ′ coherent strengthening phase, which determines the γ′ phase content, precipitation temperature, and precipitation rate. Al, the primary element in the γ′ phase, forms a protective film on the metal surface at high temperatures, enhancing the alloy's oxidation and corrosion resistance. Nb diffuses slowly, reducing the γ′ phase formation rate and precipitation temperature. However, excessive Nb content can cause severe segregation and the formation of a deleterious δ phase. Excessive Ti content can form a deleterious η phase, increasing the γ' phase dissolution temperature and narrowing the hot working window. Excessive Ta content can form a deleterious μ phase. The precipitation of deleterious phases can severely impact the high-temperature stability of the γ / γ′ coherent microstructure. Therefore, to ensure the alloy is free of deleterious phase precipitation and maintain high-temperature microstructure stability and excellent mechanical properties, while limiting the content of each element, it is important to maintain an atomic percentage ratio of (Ti+Nb+Ta) / Al of 0.5-1. The elements play a role in solid solution strengthening and corrosion resistance and oxidation resistance. Excessive addition of Cr will form σ harmful phase; Mo can reduce the notch sensitivity of the alloy; W can improve the temperature bearing capacity of the alloy on the one hand, and promote the precipitation of γ' particles in Ni-Co based high temperature alloys on the other hand, thereby improving the stability of the γ' phase; however, excessive addition of Mo and W will lead to the precipitation of harmful phases such as topological close packed phase (TCP). Elements can improve matrix stability. The large addition of Co not only reduces the dissolution temperature of the γ' phase, effectively expanding the alloy's hot working range and improving its processing deformation capability, but also significantly improves the alloy's long-term strength and creep resistance by reducing the matrix's stacking fault energy and promoting the formation of stacking faults and nanotwins. Furthermore, trace amounts of C, B, and Zr are required to refine grains and enhance grain boundary bonding. However, excessive addition of these elements can also affect the alloy's weldability, reduce its plasticity, and easily cause carboride to aggregate at grain boundaries, affecting the alloy's creep properties. Therefore, a Ni-Co based deformed high strength and high entropy high temperature alloy for 850℃ with high content of square γ′ coherent strengthening was finally determined to be: Ni-(35.1~37.7)Co-(2.6~2.7)Al-(2.8~3.3)Ti-(0.6~2.8)Nb-(0~1.3)Ta-(8.4~12.5)Cr-(2.9~3.9)Mo-(5.5~5.9)W-(0~0.08)C-(0~0.02)B-(0~0.03)Zr.

[0015] The preparation method of the present invention is as follows: high-purity metal materials are prepared according to mass percentages. The prepared materials are melted at least four times in a vacuum non-consumable arc melting furnace under argon atmosphere to obtain a 100g alloy ingot with uniform composition, with a mass loss of no more than 0.1% during the melting process; the alloy ingot is homogenized in a muffle furnace at a temperature of 1150-1200°C for 4-8 hours, followed by multiple unidirectional cold rolling passes with a single reduction of 0.1-1mm and a total reduction of 85-90%; finally, after solution treatment at 1060-1100°C for 1-2 hours, an aging treatment at 850°C for 50-500 hours is performed, and water quenching is performed to obtain an 850°C Ni-Co-based deformation high-strength and high-entropy high-temperature alloy with a high content of square γ′ coherent strengthening. The X-ray diffractometers (XRD, Cu K α The alloy's microstructure and structure were examined using a 3D laser (radiation, λ = 0.15406 nm); hardness tests were conducted at different aging times at 850°C using an HVS-1000 Vickers hardness tester; and tensile mechanical properties were tested at room temperature and 800°C using a UTM5504 electronic universal tensile testing machine. This confirms that the present invention is a Ni-Co-based deformable high-strength, high-entropy superalloy for use at 850°C with high-content square γ′ coherent strengthening. The alloy composition by weight (wt.%) is: Co: 35.1-37.7, Al: 2.6-2.7, Ti: 2.8-3.3, Nb: 0.6-2.8, Ta: 0-1.3, Cr: 8.4-12.5, Mo: 2.9-3.9, W: 5.5-5.9, C: 0-0.08, B: 0-0.02, Zr: 0-0.03, Ni: balance, and the atomic percentage ratio of (Ti+Nb+Ta) / Al is 0.5-1. The material's microstructure and performance indicators are: room temperature yield strength σ s >1000MPa, tensile strength σ b >1400MPa, elongation δ>25%; high temperature yield strength σ at 800℃ s >850MPa; After aging, this series of alloys exhibits coherent precipitation of square γ′ nanoparticles on the FCC-γ matrix, with the total volume percentage of the γ′ phase being 45-60%. After long-term aging at 850°C / 500h, there is no significant coarsening of the γ′ particles and no harmful phase formation, the γ / γ′ coherent structure is stable, and the alloy hardness is stable at 390-470kgf·mm -2 between.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] (1) The present invention is based on the cluster composition formula method developed by the applicant to design and develop a Ni-Co based deformable high-strength and high-entropy superalloy for 850°C with high content of square γ′ coherent strengthening. Compared with existing deformable superalloys, the total volume percentage of γ′ phase of the present invention is 45-60%, which is higher than many current representative deformable superalloys, such as Waspaloy alloy (30-35%), IN718Plus alloy (15-25%) and U720Li alloy (40-44%). At the same time, the alloy has good deformation processing ability and simple preparation process.

[0018] (2) The microstructure of this series of high-content square γ′ coherent strengthened Ni-Co based deformed high-strength and high-entropy high-temperature alloys for use at 850℃ is characterized by the coherent precipitation of square L12-γ′ nanoparticles on the FCC-γ matrix, and the γ′ nanoparticles are evenly distributed on the matrix with a volume fraction of 45-60%. The series of alloys can maintain the stability of the γ / γ′ coherent structure after long-term aging at 850℃, and have excellent high-temperature structure stability. At the same time, the high-temperature strength of the series of alloys at 800℃ exceeds 850MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the SEM microstructure of the alloy prepared in Example 1: Figure 1 This is the microstructure morphology after aging at 850℃ for 50h, that is, square γ′ nanoparticles are coherently precipitated on the FCC-γ matrix, and the γ′ nanoparticles are about 90nm.

[0020] Figure 2 This is the SEM microstructure of the alloy prepared in Example 1: Figure 2 This is the microstructural morphology after aging at 850℃ for 500h, that is, square γ′ nanoparticles are coherently precipitated on the FCC-γ matrix, and the γ′ nanoparticles are about 200nm. DETAILED DESCRIPTION

[0021] The specific implementation of the present invention is described in detail below in conjunction with the technical solution.

[0022] Example 1:

[0023] Ni-37.38Co-2.60Al-2.99Ti-0.61Nb-1.18Ta-8.42Cr-3.89Mo-5.61W-0.08C (wt.%) alloy

[0024] Step 1: Alloy preparation

[0025] High-purity metal materials are used, and the ingredients are proportioned according to mass percentage. The ingredients are repeatedly smelted five times in a vacuum non-consumable arc melting furnace under argon atmosphere to obtain a 100g alloy ingot with uniform composition. The mass loss during the smelting process does not exceed 0.1%. The alloy ingot is homogenized in a muffle furnace at 1200℃ / 4h and water quenched. The purpose of the homogenization treatment is to reduce or eliminate component segregation and dissolve uneven precipitates. It is then cold-rolled in multiple passes with a single reduction of 0.8mm and a total reduction of 90%. Finally, after solution treatment at 1080℃ / 1h, it is aged at 850℃ for 50h and water quenched.

[0026] Step 2: Alloy density, structure and mechanical properties testing

[0027] The microstructure and structure of the alloy after aging treatment were examined by OM, SEM and XRD. The results showed that the microstructure of the present invention is square γ' nanoparticles coherently precipitated on the FCC-γ matrix, and the γ' particles can be stably present for a long time at 850°C. After aging for 50 hours, the size of the γ' nanoparticles is 90nm, and after aging for 500 hours, the size of the γ' nanoparticles is 200nm, and the volume percentage is stable at 50%. The microstructure morphology is shown in the attached figure. Figure 1 、 2 As shown; the hardness test was carried out using a Vickers hardness tester, and the aging was carried out at 850℃ for 100h, 200h, and 500h respectively. The hardness HV = 420 ± 10kgf·mm -2 Basically unchanged; the tensile properties at room temperature and 800 ° C were measured using an MTS universal tensile testing machine: room temperature yield strength σ s =1026MPa, tensile strength σ b =1499MPa, elongation after fracture δ = 25.5%; high temperature yield strength σ at 800℃ s =872MPa.

[0028] Example 2:

[0029] Ni-37.68Co-2.65Al-2.82Ti-0.68Nb-1.32Ta-8.44Cr-3.06Mo-5.88W (wt.%) alloy

[0030] Step 1: Alloy preparation

[0031] High-purity metal materials are used, and the ingredients are proportioned according to mass percentage. The ingredients are repeatedly melted four times in a vacuum non-consumable arc melting furnace under argon atmosphere to obtain a 100g alloy ingot with uniform composition, with a mass loss of no more than 0.1% during the melting process. The alloy ingot is homogenized in a muffle furnace at 1180℃ / 6h and water quenched. The purpose of homogenization treatment is to reduce or eliminate component segregation and dissolve uneven precipitates. It is then cold-rolled in multiple passes with a single reduction of 0.6mm and a total reduction of 87%. Finally, after solution treatment at 1100℃ / 1h, it is aged at 850℃ for 50h and water quenched.

[0032] Step 2: Alloy density, structure and mechanical properties testing

[0033] OM, SEM, and XRD analysis of the microstructure and structure of the aging alloy revealed a coherent precipitation of square γ′ nanoparticles on an FCC-γ matrix, similar to that of Example 1. Furthermore, the γ′ particles remained stable for extended periods at 850°C. After aging for 50 hours, the size of the γ′ nanoparticles decreased to approximately 100 nm, and after aging for 500 hours, the size of the γ′ nanoparticles decreased to approximately 200 nm, with a volume fraction remaining stable at approximately 47%. Vickers hardness testing revealed a hardness of HV = 400 ± 10 kgf·mm after aging at 850°C for 100, 200, and 500 hours, respectively. -2 Basically unchanged; the tensile properties at room temperature and 800 ° C were measured using an MTS universal tensile testing machine: room temperature yield strength σ s =1005MPa, tensile strength σ b =1484MPa, elongation after fracture δ=28.2%; high temperature yield strength σ at 800℃ s =856MPa.

[0034] Example 3:

[0035] Ni-35.10Co-2.69Al-3.31Ti-2.78Nb-12.49Cr-2.89Mo-5.49W-0.08C-0.02B-0.03Zr (wt.%) alloy

[0036] Step 1: Alloy preparation

[0037] High-purity metal materials are used, and the ingredients are proportioned according to mass percentage. The ingredients are repeatedly smelted six times in a vacuum non-consumable arc melting furnace under argon atmosphere to obtain a 100g alloy ingot with uniform composition. The mass loss during the smelting process does not exceed 0.1%. The alloy ingot is homogenized in a muffle furnace at 1150℃ / 2h + 1180℃ / 3h, and water quenched. The purpose of the homogenization treatment is to reduce or eliminate component segregation in the structure and dissolve uneven precipitates. It is then cold-rolled in multiple passes, with a single reduction of 0.4mm and a total reduction of 85%. Finally, after solution treatment at 1070℃ / 2h, it is aged at 850℃ for 50h and water quenched.

[0038] Step 2: Alloy density, structure and mechanical properties testing

[0039] OM, SEM, and XRD analysis of the microstructure and structure of the aging alloy revealed a coherent precipitation of square γ' nanoparticles on an FCC-γ matrix, similar to that of Example 1. Furthermore, the γ' particles remained stable for extended periods at 850°C. After aging for 50 hours, the size of the γ' nanoparticles decreased to approximately 100 nm, and after aging for 500 hours, the size of the γ' nanoparticles decreased to approximately 190 nm, with a stable volume fraction of approximately 58%. Vickers hardness testing revealed a hardness of 460 ± 10 kgf·mm (HV) after aging at 850°C for 100, 200, and 500 hours, respectively. -2 Basically unchanged; the tensile properties at room temperature and 800 ° C were measured using an MTS universal tensile testing machine: room temperature yield strength σ s =1117MPa, tensile strength σ b =1594MPa, elongation after fracture δ=28.7%; high temperature yield strength σ at 800℃ s =950MPa.

[0040] Example 4:

[0041] Ni-36.21Co-2.70Al-2.99Ti-1.23Nb-0.88Ta-10.86Cr-3.06Mo-5.74W-0.02C-0.01B-0.02Zr (wt.%) alloy

[0042] Step 1: Alloy preparation

[0043] High-purity metal materials are used, and the ingredients are proportioned according to mass percentage. The ingredients are repeatedly melted eight times in a vacuum non-consumable arc melting furnace under argon atmosphere to obtain a 100g alloy ingot with uniform composition, with a mass loss of no more than 0.1% during the melting process. The alloy ingot is homogenized in a muffle furnace at 1170℃ / 6h and water quenched. The purpose of the homogenization treatment is to reduce or eliminate component segregation and dissolve uneven precipitates. It is then cold-rolled in multiple passes with a single reduction of 0.4mm and a total reduction of 87%. Finally, after solution treatment at 1060℃ / 1.5h, it is aged at 850℃ for 50h and water quenched.

[0044] Step 2: Alloy density, structure and mechanical properties testing

[0045] OM, SEM, and XRD analysis of the microstructure and structure of the aging alloy revealed a coherent precipitation of square γ' nanoparticles within an FCC-γ matrix, similar to that of Example 1. Furthermore, the γ' particles remained stable for extended periods at 850°C. After aging for 50 hours, the γ' nanoparticles reached a size of approximately 95 nm, and after aging for 500 hours, the γ' nanoparticles reached a size of approximately 190 nm, with a stable volume fraction of approximately 53%. Vickers hardness testing revealed a hardness of 440 ± 10 kgf·mm (HV) after aging at 850°C for 100, 200, and 500 hours, respectively. -2 Basically unchanged; the tensile properties at room temperature and 800 ° C were measured using an MTS universal tensile testing machine: room temperature yield strength σ s =1036MPa, tensile strength σ b =1520MPa, elongation after fracture δ=27.9%; high temperature yield strength σ at 800℃ s =910MPa.

[0046] The above-described embodiments merely express the implementation methods of the present invention, but should not be understood as limiting the scope of the patent of the present invention. It should be pointed out that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention, which all fall within the scope of protection of the present invention.

Claims

1. A Ni-Co based deformed high strength and high entropy superalloy for use at 850°C with high content of square γ′ coherent strengthening, characterized in that: The deformed high-strength and high-entropy high-temperature alloy includes Ni, Co, Al, Ti, Nb, Ta, Cr, Mo, W, C, B, and Zr elements. The mass percentages of the alloy components are as follows: Co: 35.1-37.7, Al: 2.6-2.7, Ti: 2.8-3.3, Nb: 0.6-2.8, Ta: 0-1.3, Cr: 8.4-12.5, Mo: 2.9-3.9, W: 5.5-5.9, C: 0-0.08, B: 0-0.02, Zr: 0-0.03, Ni: balance, and the atomic percentage ratio of (Ti+Nb+Ta) / Al is 0.5-1.

2. The Ni-Co based deformed high strength and high entropy superalloy for use at 850°C with high content of square γ′ coherent strengthening according to claim 1, characterized in that: The 850°C Ni-Co-based deformable high-strength and high-entropy high-temperature alloy has a specific microstructure: square L12-γ′ nanoparticles are coherently precipitated on an FCC-γ matrix, and the total volume percentage of the γ′ phase is 45-60%. After long-term aging at 850°C, the γ / γ′ coherent microstructure remains stable, with no obvious coarsening and no harmful phase formation, and good high-temperature microstructure stability.

3. The Ni-Co based deformed high strength and high entropy superalloy for use at 850°C with high content of square γ′ coherent strengthening according to claim 1, characterized in that: Typical properties of the Ni-Co based deformable high strength and high entropy high temperature alloy for use at 850°C are: room temperature yield strength>1000MPa, room temperature elongation>25%, and high temperature yield strength>850MPa at 800°C.

4. A method for preparing a Ni-Co based deformed high strength and high entropy superalloy for use at 850°C with high square γ′ coherent strengthening according to any one of claims 1 to 3, comprising the following steps: In the first step, each alloy component is placed into a vacuum arc melting furnace according to its mass percentage and melted at least multiple times to obtain an alloy ingot with uniform composition; In the second step, the alloy ingot is homogenized using a muffle furnace; The third step is to carry out multiple passes of unidirectional cold rolling; In the fourth step, after solution treatment, aging treatment is carried out at 850°C and water quenching is carried out to obtain a Ni-Co based deformed high-strength and high-entropy high-temperature alloy for use at 850°C with a high content of square γ′ coherent strengthening.

5. The method for preparing a Ni-Co based deformed high strength and high entropy superalloy for use at 850°C with high content of square γ′ coherent strengthening according to claim 4, characterized in that: In the second step, the treatment temperature is 1150-1200° C. and the treatment time is 4-8 hours.

6. The method for preparing a Ni-Co based deformed high strength and high entropy superalloy for use at 850°C with high content of square γ′ coherent strengthening according to claim 4, characterized in that: In the third step, the single pressing amount is 0.1 to 1 mm, and the total pressing amount is 85 to 90%.

7. The method for preparing a Ni-Co based deformed high strength and high entropy superalloy for use at 850°C with high content of square γ′ coherent strengthening according to claim 4, characterized in that: In the fourth step, the temperature and time of the solution treatment are 1060-1100° C. / 1-2 h.

8. The method for preparing a Ni-Co based deformed high strength and high entropy superalloy for use at 850°C with high content of square γ′ coherent strengthening according to claim 4, characterized in that: In the fourth step, the aging treatment time is 50 to 500 hours.